GE_GERICHTE C/15817/2018 vom 14. Mai 2019 - GE Cour de justice (2019)
PROTECTION DE L'UNION CONJUGALE ; MESURE PROVISIONNELLE ; DROIT D'ÊTRE ENTENDU ; GARDE ALTERNÉE ; OBLIGATION D'ENTRETIEN ; ENFANT ; MINORITÉ(ÂGE) ; CONJOINT | CC.176.al1.let1; CC.176.al3; CC.285.al1; CC.296.al2